Transcriptomic Response to Perkinsus marinus in Two Crassostrea Oysters Reveals Evolutionary Dynamics of Host-Parasite Interactions - Chan, Jiulin; Wang, Lu; Li, Li; Mu, Kang; Bushek, David; Xu, Yue; Guo, Ximing; Zhang, Guofan; Zhang, Linlin (Frontiers in Genetics, 2021)
Infectious disease outbreaks are causing widespread declines of marine invertebrates including corals, sea stars, shrimps, and molluscs. Dermo is a lethal infectious disease of the eastern oyster Crassostrea virginica caused by the protist Perkinsus marinus. The Pacific oyster Crassostrea gigas is resistant to Dermo due to differences in the host-parasite interaction that is not well understood. We compared transcriptomic responses to P. marinus challenge in the two oysters at early and late infection stages. Dynamic and orchestrated regulation of large sets of innate immune response genes were observed in both species with remarkably similar patterns for most orthologs, although responses in C. virginica were stronger, suggesting strong or over-reacting immune response could be a cause of host mortality. Between the two species, several key immune response gene families differed in their expansion, sequence variation and/or transcriptional response to P. marinus, reflecting evolutionary divergence in host-parasite interaction. Of note, significant upregulation of inhibitors of apoptosis (IAPs) was observed in resistant C. gigas but not in susceptible C. virginica, suggesting upregulation of IAPs is an active defense mechanism, not a passive response orchestrated by P. marinus. Compared with C. gigas, C. virginica exhibited greater expansion of toll-like receptors (TLRs) and positive selection in P. marinus responsive TLRs. The C1q domain containing proteins (C1qDCs) with the galactose-binding lectin domain that is involved in P. marinus recognition, were only present and significantly upregulated in C. virginica. These results point to previously undescribed differences in host defense genes between the two oyster species that may account for the difference in susceptibility, providing an expanded portrait of the evolutionary dynamics of host-parasite interaction in lophotrochozoans that lack adaptive immunity. Our findings suggest that C. virginica and P. marinus have a history of coevolution and the recent outbreaks may be due to increased virulence of the parasite.